Body Mass Index And Survival Rate in Nasopharyngeal Cancer Patient: An Evidence-based Case Report - Yohannessa Wulandari; Metta Satyani; Marvin Marino; Nurul Ratna Mutu Manikam (Indonesian Nutrition Association, 2020)
Introduction: Nasopharyngeal cancer is the most common type of head and neck cancer with prevalence of 6.2/100000 population. Recently, study of prognostic factors for nasopharyngeal cancer still becomes one of research focuses. Several studies have tried to find the relationship between nutritional status (body mass index/BMI) and nasopharyngeal cancer patients’ survival rate, but the results are still inconsistent. Objective: To find the relationship between nutritional status represented by BMI and nasopharyngeal cancer patients’ survival rate.Methods: Electronic literature searches were performed in Cochrane®, Scopus®, and Pubmed®. Mesh term and title/abstracts were screened based on inclusion and exclusion criteria before relevant journals were reviewed.Results: Two articles were selected based on the eligibility criteria and relevancy to the clinical question. In the study of Huang et al., the subject was nasopharyngeal cancer patient stage III and IV was included as subject of the study. In the study of Lin et al., nasopharyngeal cancer patient with metastases was also included. Patient with higher BMI has better survival rate than underweight BMI category.Conclusion: Increasing BMI in underweight cancer patient simproves nasopharyngeal cancer patient’ survival rate.